Zirconia reinforcement of cement free Alumina refractory castables by two routes - Rendtorff Birrer, Nicolás Maximiliano (2012)
The cement free castables (CFC) and the ultra low cement castables (ULCC) differ from the conventional castables not only in the fact that alumina cement content and that the water required for elaboration is considerable lower, but also that they exhibit outstanding physical-chemical properties and mechanical properties. In this work we compared two routes of introducing zirconia to cement free alumina castables with a zirconia free castables, one by adding electrofused zirconia grains and the second by incorporating reused grains from electrofused AZS block formerly used as floor of glass melting furnaces. Comparable microstructures and textural properties were achieved, this fact permitted to evaluate the zirconia influence in the mechanical and fracture properties of the studied materials. There was a direct correlation with the zirconia content of both the mechanical properties at room temperature and at high temperatures (1350°C). Finally, while at room temperature the incorporation of AZS grains proved to be more efficient to reinforce electrofused zirconia proved to be the most effective additive for reinforcement of castables studied if they were to be used at elevated temperatures.